Thomas Hirschhorn : Deleuze monument - Dezeuze, Anna.; Hirschhorn, Thomas (London : Afterall Books, 2014)
"Thomas Hirschhorn's Deleuze monument was conceived for 'La beauté' in Avignon in 2000. It comprised four elements: a rock inscribed with a quotation, an altar, a monumental sculpture and a library including books by and about Deleuze. Located in the Cité Champfleury, outside Avignon's historical walls, Deleuze monument embodied Hirschhorn's desire to put his work 'in a difficult situation' between reality, politics and aesthetics, and marks a significant turning point in his approach to producing and maintaining public works"--P. 4 of cover.
boek
Keywords: Hirschhorn, Thomas; Deleuze, Gilles, -- 1925-1995 -- Monuments -- France -- Avignon; Interactive art -- France -- Avignon